Association of Underweight and Weight Loss With Poor Prognosis and Poor Therapy Effectiveness in Brain Metastases: A Retrospective Study - He, Yan; Zhang, Yu; Chong, Weelic; Pei, Yiyan; Zhang, Renjie; Liu, Zheran; Yu, Jiayi; Peng, Xingchen; Fang, Fang (Frontiers in Nutrition, 2022)
Background The prognostic role of body mass index (BMI) in patients with brain metastases is controversial. We aim to investigate the impact of BMI on prognosis and anti-cancer therapy effectiveness in brain metastases. Methods Patients diagnosed with brain metastases between Oct 2010 and July 2019 were followed for mortality through April 2021. The prognostic role of BMI on overall survival was assessed by a restricted cubic spline using a flexibly model to visualize the relationship between the BMI values and hazard ratios of all-cause mortality, followed by a cox regression model. The disparity of survival outcome in patients receiving anti-cancer therapies or not was evaluated according to the classification of BMI. Results A total of 2,466 patients were included in the analysis, including 241 in the underweight (BMI < 18.5 kg/m2) group, 1503 in the normal weight group (BMI 18.5-23.9 kg/m2) and 722 in the overweight (BMI ≥24.0 kg/m2) group. Relative to the normal weight group, underweight patients were associated with poor prognosis (adjusted-HR 1.25, 95% CI 1.07-1.46, p=0.005). However, those in the overweight group showed similar overall survival when compared to the normal weight group. Patients with weight loss were associated with a higher risk of mortality compared with patients without significant weight loss. In underweight patients, there was an insignificant difference in survival outcome whether they received anti-cancer therapies or not. Conclusions Underweight and significant weight loss were associated with poor prognosis in brain metastases. Meanwhile, anti-cancer therapies did not significantly improve overall survival in underweight patients. These findings suggest that improving nutrition to maintain body weight is critical for patients with brain metastases.